The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18533/ijbsr.v6i2.916
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Job Status and Whistle-Blowing: Evidence from Micro-Finance Companies

Abstract: We investigate the effect of religiosity and job status on whistle-blowing among employees of micro finance companies in Ga-East district of Ghana. The intellectual dimension of religiosity informs and produces high sense of morality in an individual thus influencing whistle-blowing. Additionally, religion create the platform for building belief in certain rules and regulations as right or as wrong. Using quantitative approach for analyzing the effect between independent variables (job status and religiosity) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(25 reference statements)
0
1
0
1
Order By: Relevance
“…Our aim is to investigate the relationship between religious obligation and whistleblowing intention among employees in Halal food companies. Several previous studies showed a positive relationship between religious obligation and whistleblowing intention (Fitri, 2019;Puni et al, 2016;Toker Gokce, 2015). However, Yudha and Rizal (2018) found no significant relationship between whistleblowing intention and religion, as religious respondents reported a low desire to report wrongdoing.…”
Section: Religious Obligationmentioning
confidence: 84%
“…Our aim is to investigate the relationship between religious obligation and whistleblowing intention among employees in Halal food companies. Several previous studies showed a positive relationship between religious obligation and whistleblowing intention (Fitri, 2019;Puni et al, 2016;Toker Gokce, 2015). However, Yudha and Rizal (2018) found no significant relationship between whistleblowing intention and religion, as religious respondents reported a low desire to report wrongdoing.…”
Section: Religious Obligationmentioning
confidence: 84%
“…Hasil tersebut mengindikasikan bahwa mahasiswa yang memiliki tingkat religiusitas yang tinggi semestinya memiliki intensi untuk melakukan whistleblowing. Hasil yang diperoleh konsisten dengan penelitian Indrasari dan Wardhana (2020); Pulungan (2019); Puni et al (2016); Puspitosari (2019) yang memperoleh hasil bahwa segala bentuk perilaku yang kontras dengan etika akan ditolak oleh orang-orang yang memiliki nilai religiusitas yang tinggi, karena orang-orang tersebut merasa terganggu dan tidak nyaman atas pelanggaran yang mereka ketahui. Fraud yang dianggap sebagai tindakan tidak etis yang tidak diajarkan dalam agama apapun akan mengarahkan orang-orang yang memiliki nilai religiusitas tersebut untuk menolaknya, salah satunya dengan melakukan tindakan whistleblowing.…”
Section: Pengaruh Religiusitas Terhadap Niat Melakukan Whistleblowingunclassified